IMPROVING THE QUALITY OF EDUCATORS AS ONE OF THE MAIN COMPONENTS OF EDUCATION IN INDONESIAN NAVAL TECHNOLOGY COLLEGE (STTAL) - As’ad Aris Mustofa; Okol Sri Suharyo; Avando Bastari (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT The Naval College of Technology (STTAL) is one of the educations implementing units within the Indonesian Navy. In charge of organizing development education programs in the field of marine defense technology. STTAL has the main task of assisting Kasal in carrying out the education required for maritime science and technology (Iptek) colleges and fostering all ranks of its strength including its organic supporting facilities and infrastructure to support the main duties of the Navy. To enhance STTAL's world-class reputation, a development concept is needed. The development concept includes education, research, community service, human resources, infrastructure and facilities and institutional capacity. However, Human Resources (HR) plays a key role in a university, namely lecturers or educators and students. Lecturers or educators play a role in HR development. Several efforts can be made to improve human resources, namely by increasing the qualifications of lecturers and increasing the academic or research abilities of lecturers with the concept of training or mentoring, including incentives or grants. In addition, improving the academic atmosphere, such as inviting guest lecturers, sharing research and education, are also things that need to be considered in human resource development. Efforts to improve the quality of educators and education personnel cannot be separated from the following important aspects, namely salaries and welfare standards that are appropriate for their lives, qualification standards, competency standards and efforts to improve them Keywords: Indonesian Naval Technology Collage, human resource development, the qualifications of lecturers